2002
DOI: 10.1034/j.1398-9995.2002.t01-1-13447.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal provocation test (NPT) with aspirin: a sensitive and safe method to diagnose aspirin‐induced asthma (AIA)

Abstract: NPT has a high sensitivity and specificity in the diagnosis of AIA. An oral provocation should be performed to confirm the result whenever the clinical situation of the patient permits it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 21 publications
1
27
0
3
Order By: Relevance
“…Milewski et al (30) and Alonso-Llamazares et al (32) found that the specificity of nasal challenge with lysineaspirin reached 95.7% and 92.5% respectively, whereas its sensitivity was 86.7% and 80%, respectively. The predictive value of a negative result of l-ASA nasal challenge was 78.6% and 89.2%, respectively (30,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Milewski et al (30) and Alonso-Llamazares et al (32) found that the specificity of nasal challenge with lysineaspirin reached 95.7% and 92.5% respectively, whereas its sensitivity was 86.7% and 80%, respectively. The predictive value of a negative result of l-ASA nasal challenge was 78.6% and 89.2%, respectively (30,32).…”
mentioning
confidence: 99%
“…The predictive value of a negative result of l-ASA nasal challenge was 78.6% and 89.2%, respectively (30,32). Subjects should give written informed consent to participate in aspirin challenges after the actual nature of the procedures has been thoroughly explained to them by the attending physician.…”
mentioning
confidence: 99%
“…Recently, Miller at al [10] also reported a high percentage of positive challenge results (45%) with 325 mg of aspirin in patients who had previously experienced a negative acoR-monitored nasal challenge with aspirin-lysine [10]. Anterior active rhinomanometry used as an objective assessment method revealed that only 16 of 20 patients with oral challenge-proven AERD (80%) had a positive nasal response to the nasal challenge with aspirinlysine [11]. These different clinical outcomes suggest that the NSAID, the objective method used to measure the changes in nasal airways, or both might have a relevant effect on the results of nasal NSAID challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative methods have been developed to enhance safety and reduce the time needed for testing. Bronchial challenges [7] and nasal challenges [8][9][10][11][12] have been developed with various NSAIDs and assessment methods. Lee et al [8] recently presented a novel method using nasal ketorolac as the challenge drug and assessing the nasal response with a peak nasal inspiratory flow (PNIF) meter.…”
Section: Introductionmentioning
confidence: 99%
“…Our results contrast with those of Pawlowicz et al [33], who observed a significant fall in FEV 1 in all the patients they evaluated. Most authors have reported only a few mild reactions, however, thus demonstrating the high safety profile of the nasal challenge test with l -ASA [7,8,10,16,34]. …”
Section: Discussionmentioning
confidence: 99%